Delta FosB regulates wheel running. - Martin Werme; Chad Messer; Lar̀s Olson; Lauren Gilden; Peter Thorén; Eric J. Nestler; Stefan Brené (2002)
DeltaFosB is a transcription factor that accumulates in a region-specific manner in the brain after chronic perturbations. For example, repeated administration of drugs of abuse increases levels of DeltaFosB in the striatum. In the present study, we analyzed the effect of spontaneous wheel running, as a model for a natural rewarding behavior, on levels of DeltaFosB in striatal regions. Moreover, mice that inducibly overexpress DeltaFosB in specific subpopulations of striatal neurons were used to study the possible role of DeltaFosB on running behavior. Lewis rats given ad libitum access to running wheels for 30 d covered what would correspond to approximately 10 km/d and showed increased levels of DeltaFosB in the nucleus accumbens compared with rats exposed to locked running wheels. Mice that overexpress DeltaFosB selectively in striatal dynorphin-containing neurons increased their daily running compared with control littermates, whereas mice that overexpress DeltaFosB predominantly in striatal enkephalin-containing neurons ran considerably less than controls. Data from the present study demonstrate that like drugs of abuse, voluntary running increases levels of DeltaFosB in brain reward pathways. Furthermore, overexpression of DeltaFosB in a distinct striatal output neuronal population increases running behavior. Because previous work has shown that DeltaFosB overexpression within this same neuronal population increases the rewarding properties of drugs of abuse, results of the present study suggest that DeltaFosB may play a key role in controlling both natural and drug-induced reward.